Knowledge regarding diabetes and its medication among patients with diabetes mellitus visiting Okhaldhunga Community Hospital, Okhaldhunga - Bom, Rabin; Pal, Anjila; Shakya, Namo Buddha (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Diabetes mellitus is an emerging worldwide health problem. Nepal is a developing country where most of the people reside in rural areas. This study was done to assess the knowledge regarding diabetes and its medication among patients with diabetes mellitus visiting Okhaldhunga Community Hospital, Okhaldhunga, in the rural eastern part of Nepal.Method: A cross-sectional study was conducted among the diabetes mellitus patients presenting to Okhaldhunga Community Hospital during the period of 5 months (January 18 to June 18, 2019). Informed and written consent was taken from the patients followed by interviews and questionnaires. Data was entered in Microsoft Excel 10 and analyzed using SPSS version 16.0.Result: A total of 74 patients were included in the study of which 48.6% were male and 51.4% female. Most of the diabetic patients were in the age group of 50-59 years. The study shows that 98.6% had inadequate knowledge and 1.4% had moderate knowledge about diabetes mellitus. 2.8% had moderate knowledge and 97.2% had inadequate knowledge about anti-diabetic medication. A total of 32.4% of patients did not know the name of their anti-diabetic medications and 18.9% of patients did not know the time of intake of their anti-diabetic medications. A total of 75.7% of patients did not know the side effects of their anti-diabetic medications.Conclusion: Knowledge of diabetes and its medication among diabetes patients is inadequate. Healthcare providers should focus on the necessity and importance of awareness programs, patient counseling, and education to improve knowledge on diabetes.